Clinical Patterns of Spontaneous Recovery of Paralyzed Triceps Brachii Associated with C5 to C7 Injuries of the Brachial Plexus - Flores, Leandro Pretto (Journal of Reconstructive Microsurgery, 2012)
Some patients who sustain C5 to C7 nerve root injuries may demonstrate a natural recovery of elbow extension via the lower trunk; however the surgical effect of the reinnervation of the triceps brachii in such cases is still unknown. This study aims to determine the incidence of spontaneous recovery of the tricipital function and to identify the clinical and/or radiological predictors of poor spontaneous functional rehabilitation of elbow extension resulting from injuries of the upper roots of the brachial plexus. We conducted a review of the charts of 24 subjects sustaining an upper trunk syndrome with complete elbow extension palsy and who did not undergone any intervention for reinnervation of the triceps brachii in the primary brachial plexus surgery. Two years posttrauma, the muscle was scored as M0 in 12 patients (50%), M1 in 3 (12.5%), M2 in 1 (4.1%), M3 in 4 (16.6%), and M4 in 4 subjects (16.6%). The number of avulsed roots and the preoperative power of the latissimus dorsi did not demonstrate any significance in predicting the outcome of spontaneous elbow extension recovery; whereas the preoperative paralysis of the muscles for wrist extension was determined to be reliable predictive parameter for poor natural recovery of tricipital function.
Keywords: brachial plexus; triceps; elbow extension